On the social appropriateness of discrimination - Abigail Barr; Tom Lane; Daniele Nosenzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
Understanding what motivates discrimination is of importance to economists and social scientists in general. In this paper, the authors address whether the taste to discriminate against outsiders is related to social norms. Recent studies have shown various different types of economic behaviour are more likely to occur when they are perceived to be more socially appropriate. The theoretical work of Akerlof and Kranton (2000, 2005) suggests discrimination will also be stronger when social norms favour it. This paper tests whether such a relationship exists. In this Nottingham School of Economics working paper, Abigail Barr, Tom Lane and Daniele Nosenzo use experimental methods to address the question. They find participants perceive it to be more socially appropriate to discriminate on the basis of social identities artificially induced, using a trivial minimal group technique, than on the basis of nationality, a natural social identity. Correspondingly, they find that participants discriminate more in the artificial identity setting. These results suggest social norms, and the preference to comply with them, do indeed affect discriminatory decisions, and that the social inappropriateness of discrimination can help reduce discriminatory behaviour.
Keywords: C71; C92; D03; 330; discrimination; social norms; Krupka-Weber method; allocator game